New Phenolic Compounds with Anti-adipogenic Activity from the Aerial Parts of Pulsatilla koreana - Liu, Qing; Ahn, Jong Hoon; Kim, Seon Beom; Hwang, Bang Yeon; Lee, Mi Kyeong (Planta Medica, 2012)
Three new phenolic compounds, pulsatillosides A (1), B (2), and C (3), were isolated from the aerial parts of Pulsatilla koreana, together with two known flavonoid glycosides, trans-tiliroside (4) and kaempferol-3-O-β-glycoside (5). The structures of the isolated compounds were determined on the basis of spectroscopic analysis including 1D, 2D NMR and HR-MS. Among the isolated compounds, compounds 1–3 significantly inhibited adipocyte differentiation as measured by fat accumulation in 3 T3-L1 cells using Oil Red O staining.
Keywords: Pulsatilla koreana; Ranunculaceae; pulsatillosides A–C; adipocyte differentiation